Development of an IoT-based smart agricultural system for environmental monitoring and soil condition using raspberry pi and mobile interface - Md Ralib @ Md Raghib, Aliza 'Aini; Mazlan, Amir Zakwan; Abd. Rahman, Faridah (IEEE, 2025)
he growing global population, expected to reach 9.8 billion by 2050, places immense pressure on food production and highlights the urgency of addressing food security and crop wastage. Traditional agricultural practices, which rely heavily on manual observation and farmer intuition, are increasingly insufficient due to labor shortages, inefficiency, and inconsistency in monitoring accuracy. This paper presents the development of an IoT-based smart agricultural system for real-time environmental and soil condition monitoring to support precision farming. The objective is to develop an IoT based smart agricultural system for environmental monitoring and soil condition using Raspberry Pi and mobile interface. The system integrates a plant monitoring chamber with DHT22 sensors for temperature and humidity, TSL2591 for light intensity, and YL69 for soil moisture. Sensor data is collected via Raspberry Pi units and transmitted to Blynk Cloud to be displayed through a mobile application and web interface. The result shows consistent readings of four sensor parameters over a two-day measurement. This approach aims to reduce crop losses, optimize growing conditions, and enhance overall agricultural productivity, offering a scalable solution especially beneficial for small-scale and remote farming operations.